1999
DOI: 10.1002/(sici)1098-1136(19990201)25:3<240::aid-glia4>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TPA on aquaporin 4 mRNA expression in cultured rat astrocytes

Abstract: Aquaporin 4 (AQP4) is a predominant water channel protein in mammalian brains, localized in the astrocyte plasma membrane. The regulation of AQP4 is believed to be important for the homeostasis of water in the brain, but the AQP4 regulatory mechanisms are not yet known. In this study, we investigated the effect of a protein kinase C (PKC) activator on the expression of AQP4 mRNA in cultured rat astrocytes. Cultured rat astrocytes constitutively expressed AQP4 mRNA. Treatment of the cells with 0.1 microM of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Our findings are consistent with those of in-vitro studies demonstrating that PKC activators inhibit AQP4 activity , and also to downregulates the expression of AQP4 protein (Yamamoto et al, 2001), and AQP4 mRNA (Nakahama et al, 1999). However, the experimental model used may also affect the changes seen in AQP4 expression.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings are consistent with those of in-vitro studies demonstrating that PKC activators inhibit AQP4 activity , and also to downregulates the expression of AQP4 protein (Yamamoto et al, 2001), and AQP4 mRNA (Nakahama et al, 1999). However, the experimental model used may also affect the changes seen in AQP4 expression.…”
Section: Discussionsupporting
confidence: 91%
“…PKC serves as a second messenger for G-protein receptors, which are coupled to the phosphoinositide pathway, causing either a transient rise in intracellular Ca 2þ through inositol triphoshate, or activation of PKC through diacylglycerol. The phorbol ester and known PKC activator 12-Otetradecanoylphorbol 13-acetate has been found to decrease AQP4 mRNA in cultured rat astrocytes, but prolonged treatment eliminated the subsequent decrease in AQP4 mRNA (Nakahama et al, 1999;Yamamoto et al, 2001). Since pre-treatment with cycloheximide did not eliminate the reduction of AQP4 mRNA, PKC may be involved in AQP4 regulation on the transcriptional level, rather than affecting de novo protein synthesis.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…in addition to applying aQP4 rna interference to reduce the aQP4 protein level, we also used the aQP4 inhibitor phorbol 12-myristate 13-acetate (PMa) which activates protein kinase c (PKc) and inhibits aQP4 expression (22). the results of Western blotting showed that the expression of AQP4 was significantly reduced with treatment of PMA (1 and 5 µM) compared to the control cells (Fig.…”
Section: A B Cmentioning
confidence: 99%